The Effectiveness of HPT Muhammadiyah Studies in Increasing the Understanding of Kaifiyat Thoharoh Residents of Wonosari Kalimojosari Doro - Gigih Setianto (Riwayat: Educational Journal of History and Humanities, 2023)
There are still many Muhammadiyah members who do not understand the HPT Muhammadiyah, even though the HPT Muhammadiyah is a guideline for carrying out the worship of Muhammadiyah members. Pimpinan Ranting Muhammadiyah Wonosari Kalimojosari Doro Pekalongan, conducted a HPT study to increase people's understanding of worship. This study aims to determine the effectiveness of the HPT Muhammadiyah study in increasing the understanding of the kaifiyat thoharoh residents of Wonosari Kalimojosari Doro and to find out the supporting and inhibiting factors in the HPT Muhammadiyah study. This research includes the type of qualitative descriptive research. Collecting data through observation, interviews (Interview) and documentation study. Then the data were analyzed through data reduction, data presentation and conclusions. The results of this study indicate that the HPT Muhammadiyah study is effective in increasing the understanding of the kaifiyat thoharoh residents of Wonosari, Kalimojosari, Doro. The supporting factors for the well-organized HPT Muhammadiyah study include the presence of competent speakers in Islamic Fiqh according to HPT Muhammadiyah, discussion of the material in accordance with small themes so that the focus, strategy and study methods are interesting with more emphasis on lectures and questions and answers, explanation of the material in depth by including reasons and arguments, and study participants are invited to practice as learning as well as evaluation. While the inhibiting factor is the unavailability of supporting media such as LCD projectors which can actually increase the understanding of study participants through visualization. Then there are also not enough reference books that can be used as reading material for study participants.Keywords: study, HPT Muhammadiyah, understanding, thoharoh.